The doctorate as an original contribution to knowledge: Considering relationships between originality, creativity, and innovation - Baptista, Ana; Frick, Liezel; Holley, Karri; Remmik, Marvi; Tesch, Jakob; Åkerlind, Gerlese (Frontline Learning Research, 2015)
This article explores the meaning of originality in doctoral studies and its relationship with creativity and innovation. Doctoral theses are expected to provide an original contribution to knowledge in their field all over the world. However, originality is not well defined. Using the literature on concepts of originality as a foundation, this article shows that originality is not a concept commonly understood. Creativity introduces a focus on the production of knowledge, which is not just novel but also meaningful. Innovation is becoming of increasing importance in doctoral theses with the societal shift to knowledge-based economies and introduces the requirement of immediate relevance for economic purposes in doctoral education. While the three elements appear to be substantial building blocks of the potential contribution doctoral work can make in the 21st century, it is unclear the extent to which doctoral theses fulfil these expectations. The article discusses this problem with a focus on implications for doctoral education.